Justified. Season 6 [videorecording (Blu-Ray)] - Olyphant, Timothy; Searcy, Nick; Carter, Joelle; Pitts, Jacob; Tazel, Erica; Leonard, Elmore, 1925-2013 (Sony Pictures Home Entertainment, 2015)
Raylan sets out to find out more about the mysterious group buying up land in Harlan, Boyd tries to make a profit off the ledger from the bank heist, and Ava is stuck in the middle of everything.